CC16 augmentation reduces exaggerated COPD-like disease in Cc16-deficient mice - Joselyn Rojas-Quintero; Maria Eugenia Laucho-Contreras; Xiaoyun Wang; Quynh-Anh Fucci; Patrick R. Burkett; Se-Jin Kim; Duo Zhang; Yohannes Tesfaigzi; Yuhong Li; Abhiram R. Bhashyam; Zhang Li; Haider Khamas; et al. (JCI Insight, 2023)
Low Club Cell 16 kDa protein (CC16) plasma levels are linked to accelerated lung function decline in patients with chronic obstructive pulmonary disease (COPD). Cigarette smoke–exposed (CS-exposed) Cc16–/– mice have exaggerated COPD-like disease associated with increased NF-κB activation in their lungs. It is unclear whether CC16 augmentation can reverse exaggerated COPD in CS-exposed Cc16–/– mice and whether increased NF-κB activation contributes to the exaggerated COPD in CS-exposed Cc16–/– lungs. CS-exposed WT and Cc16–/– mice were treated with recombinant human CC16 (rhCC16) or an NF-κB inhibitor versus vehicle beginning at the midpoint of the exposures. COPD-like disease and NF-κB activation were measured in the lungs. RhCC16 limited the progression of emphysema, small airway fibrosis, and chronic bronchitis-like disease in WT and Cc16–/– mice partly by reducing pulmonary inflammation (reducing myeloid leukocytes and/or increasing regulatory T and/or B cells) and alveolar septal cell apoptosis, reducing NF-κB activation in CS-exposed Cc16–/– lungs, and rescuing the reduced Foxj1 expression in CS-exposed Cc16–/– lungs. IMD0354 treatment reduced exaggerated lung inflammation and rescued the reduced Foxj1 expression in CS-exposed Cc16–/– mice. RhCC16 treatment reduced NF-κB activation in luciferase reporter A549 cells. Thus, rhCC16 treatment limits COPD progression in CS-exposed Cc16–/– mice partly by inhibiting NF-κB activation and represents a potentially novel therapeutic approach for COPD.